2009
DOI: 10.1167/iovs.08-2437
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes 4q28.3 and 7q31.2 as New Susceptibility Loci for Comitant Strabismus

Abstract: This study suggests multiple susceptibility loci for comitant strabismus. The loci at chromosomes 4q28.3 and 7q31.2 show a significant evidence of linkage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
1
32
0
4
Order By: Relevance
“…Genome-wide linkage analysis of comitant strabismus has yielded relatively few chromosomal susceptibility loci. An initial study found loci at chromosomes 7p22.1 (Parikh et al, 2003) and a more recent study (Shaaban et al, 2009), extending previous work by Fujiwara et al (2003), identified loci at 4q28.3 and 7q3.1. This second study, conducted in 55 Japanese families with at least two cases of comitant strabismus, did not distinguish these cases based on the direction of their deviation.…”
Section: Discussionsupporting
confidence: 80%
“…Genome-wide linkage analysis of comitant strabismus has yielded relatively few chromosomal susceptibility loci. An initial study found loci at chromosomes 7p22.1 (Parikh et al, 2003) and a more recent study (Shaaban et al, 2009), extending previous work by Fujiwara et al (2003), identified loci at 4q28.3 and 7q3.1. This second study, conducted in 55 Japanese families with at least two cases of comitant strabismus, did not distinguish these cases based on the direction of their deviation.…”
Section: Discussionsupporting
confidence: 80%
“…Another study from Japan has been done to localize the chromosomal susceptibility loci for comitant strabismus. [9] They found multiple susceptibility loci for comitant strabismus. Chromosome 8q[10] has been shown to be associated with DRS.…”
Section: Etiologymentioning
confidence: 99%
“…In Japan, Matsuo and colleagues recruited 55 families in which comitant strabismus was present in at least two family members. 10 Their linkage analysis identified loci at 4q28.3 and 7q31.2. Some of the genes that lie within these regions encode proteins expressed in the brain such as neuronal cell adhesion molecule, as might be expected from theories purporting that strabismus is caused by a neurological deficit that compromises the capacity for binocular fusion and stereopsis.…”
Section: Linkage Analysismentioning
confidence: 99%